Separation and identification of differentially expressed nuclear matrix proteins between human esophageal immortalized and carcinomatous cell lines - Xiong, Xing-Dong (World J Gastroenterol, 2003)
AIM: To separate and identify differentially expressed nuclear matrix proteins (NMPs) between the immortalized human esophageal epithelial cell line (SHEE) and the malignantly transformed esophageal carcinoma cell line (SHEEC), and to provide new ways for finding specific markers and the pathogenesis of esophageal carcinoma. METHODS: SHEE and SHEEC cell lines were used to extract NMPs. The quality of NMPs was monitored by Western blot analysis including DNA topoisomerase IIα, proliferation cell nuclear antigen (PCNA) and histone. NMPs of SHEE and SHEEC were analyzed by two-dimensional electrophoresis (2-DE), silver staining and PDQuest6.2 image analysis software. Three spots in which the differentially expressed NMPs were more obvious, were selected and analyzed with matrix-assisted laser desorption/ionization time of flying mass spectrometry (MALDI-TOF-MS) and database search. RESULTS: Western blot analysis revealed that DNA topoisomerase IIα and PCNA were detected, and the majority of histones were deleted in NMPs of SHEE and SHEEC. After 2-DE image analysis by PDQuest6.2 software, the 2-DE maps were detected with an average of 106 ± 7.1 spots in SHEE and 132 ± 5.0 spots in SHEEC. Most of them were matched one another (r = 0.72), only 16 protein spots were found differing in intensity. Three NMPs including cytoskeletal tropomyosin, FK506-binding protein 6, similar to retinoblastoma binding protein 8 were preliminarily identified by MALDI- TOF-MS. CONCLUSION: These differentially expressed NMPs may play an important role during malignant transformation from SHEE to SHEEC. Their separation and identification will contribute to searching for specific markers and probing into the pathogenesis of esophageal carcinoma.